Strategi Humas Kemendikbudristek dalam Menyosialisasikan Kebijakan Merdeka Belajar kepada Sidina Community - Syifa Albalqis Danayomi; Christina Tri Hendriyani (Jurnal Komunikasi Massa, 2024)
The Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) is the ministry responsible for the education sector in Indonesia. During Nadiem Makarim's tenure, Kemendikbudristek introduced a new policy in the field of education called the "Merdeka Belajar" policy. This policy is regarded as a transformative initiative in Indonesia's education system. To disseminate the Merdeka Belajar policy, Kemendikbudristek sought the assistance of change agents, including Sidina Community. Kemendikbudristek considers Sidina Community to be a vital player in the Merdeka Belajar initiative as its members are parents of students directly affected by the policy. This research aims to understand the communication strategy employed by the Public Relations Division of the Ministry of Education, Culture, Research, and Technology in socializing the Merdeka Belajar policy to Sidina Community as one of the change agents. The study is a qualitative case study, utilizing data collection techniques such as interviews, literature review, and observation. The findings indicate that the communication strategy used by Kemendikbudristek’s Public Relations Division comprises four stages: planning, which incorporates the communication elements from Lasswell's model, including Who says What in Which channel to Whom with what Effect; organizing, which involves team and communicator coordination; actuating, carried out through seminars, webinars, and training; and controlling, which includes evaluation, report preparation, and stakeholder satisfaction surveys. Keywords: